Depicting People in Visual Cues Affects Alcohol Cue Reactivity in Male Alcohol-Dependent Patients - Abdulqawi Alarefi; Xunshi Wang; Rui Tao; Qinqin Rui; Guoqing Gao; Ying Wang; Liangjun Pang; Chialun Liu; Xiaochu Zhang (Brain Sciences, 2022)
Cue reactivity is often used to study alcohol cues brain responses. Standardized image sets are used, but the effect of viewing people interacting with the alcohol drink remains unclear, which is associated with the factors of alcohol cues that influence the degree of response to alcohol stimuli. The present study used fMRI to investigate the reactivity of alcohol dependence (AD) inpatients to alcohol cues with or without human drinking behavior. Cues with a human interacting with a drink were hypothesized to increase sensorimotor activation. In total, 30 AD inpatients were asked to view pictures with a factorial design of beverage types (alcoholic vs. non-alcoholic beverages) and cue types (with or without drink action). Whole-brain analyses were performed. A correlation analysis was conducted to confirm whether the whole-brain analysis revealed cue-related brain activations correlated with problem drinking duration. The left lingual gyrus showed significant beverage types through cue type interaction, and the bilateral temporal cortex showed significant activation in response to alcohol cues depicting human drinking behavior. The right and left lingual gyrus regions and left temporal cortex were positively correlated with problem drinking duration. Sensorimotor activations in the temporal cortex may reflect self-referential and memory-based scene processing. Thus, our findings indicate these regions are associated with alcohol use and suggest them for cue exposure treatment of alcohol addiction.